2018
DOI: 10.37040/geografie2018123040461
|View full text |Cite
|
Sign up to set email alerts
|

Visitor profiling using characteristics of socio-demographic and spatial behavior as tools to support the management of protected mountain areas

Abstract: Protected mountain areas are attractive tourist destinations, and the number of visitors to these areas is increasing. The extension of cable car operations into the summer season is a challenge for some protected areas. Our study focuses on visitor profiles and is based on the characteristics of socio-demographic and spatial behavior of cable car users of the Chopok area (Slovakia). The methods used involve recording visitors’ itineraries through the use of GPS loggers and conducting post-trip interviews with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 44 publications
0
3
0
Order By: Relevance
“…In the struggle to improve the research process, authors are striving to validate new methods, mainly to ease the process and reduce or overcome the limitations of traditional instruments (time-consuming, expensive, incomplete information, human error). Some authors choose to analyse information already available on social media platforms to understand consumer behaviour [32,49,53,71], while others take a different approach, analysing GPS/PPGIS tracks to study travel patterns [55,63,65,73,80,82,90,92,94,104], and a few authors, such as Barros et al [58], use both methods.…”
Section: No Of Published Papersmentioning
confidence: 99%
“…In the struggle to improve the research process, authors are striving to validate new methods, mainly to ease the process and reduce or overcome the limitations of traditional instruments (time-consuming, expensive, incomplete information, human error). Some authors choose to analyse information already available on social media platforms to understand consumer behaviour [32,49,53,71], while others take a different approach, analysing GPS/PPGIS tracks to study travel patterns [55,63,65,73,80,82,90,92,94,104], and a few authors, such as Barros et al [58], use both methods.…”
Section: No Of Published Papersmentioning
confidence: 99%
“…As managers and planners strive for the sustainability of attractions and destinations, these notwithstanding, they commonly complement interpreters with other non-personal NI approaches [54]. These non-personal NI approaches include information centres, trails, signages, and display boards [34,[54][55][56][57].…”
Section: Nature Interpretationmentioning
confidence: 99%
“…Other studies have shown that visitors' motivations and trip characteristics are not the only factors that condition their visits to attractions. Certain studies have highlighted the relevance of the socio-economic characteristics of visitors and attractions when it comes to explaining the type of places visited by tourists [34][35][36]. Timothy [37] stated that price is one of the factors that influences visitors' movements.…”
Section: Literature Reviewmentioning
confidence: 99%